Prospective phase II trial of pazopanib plus CapeOX (capecitabine and oxaliplatin) in previously untreated patients with advanced gastric cancer - Kim, Seung Tae (Oncotarget, 2016)
We designed a single-arm, open label phase II study to determine the efficacy and toxicity of the combination of pazopanib with CapeOx (capecitabine and oxaliplatin) in metastatic /recurrent advanced gastric cancer (AGC) patients. Previously untreated AGC patients received capecitabine (850 mg/m(2) bid, day 1–14) plus oxaliplatin (130 mg/m(2), day 1) in combination with pazopanib (800 mg, day 1–21) every three weeks. Treatment was continued until progression of the disease or intolerable toxicity was observed. In all, 66 patients were treated with pazopanib plus CapeOx. The median age of the patients was 51.5 years (range, 23.0–77), and the median ECOG performance status was 1 (0–1). Among all 66 patients, one complete response and 37 partial responses were observed (overall response rate, 62.4%; 95% confidence interval (CI), 45.7–73.5% accounting for the 2-stage design of this trial). Stable disease was observed in 23 patients (34.8%), revealing a 92.4% disease control rate. The median progression free survival and overall survival were 6.5 months (95% CI, 5.6–7.4) and 10.5 months (95% CI, 8.1–12.9), respectively. Thirty-four patients (51.5%) experienced a treatment-related toxicity of grade 3 or more. The most common toxicities of grade 3 or more were neutropenia (15.1%), anemia (10.6%), thrombocytopenia (10.6%), anorexia (7.6%), nausea (3.0%), and vomiting (3.0%). There were no treatment-related deaths. The combination of pazopanib and CapeOx showed moderate activity and an acceptable toxicity profile as a first-line treatment in metastatic / recurrent AGC patients (ClinicalTrials.gov NCT01130805).